2010
DOI: 10.1016/j.ijdevneu.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Solvent inhalation (toluene and n‐hexane) during the brain growth spurt impairs the maturation of frontal, parietal and occipital cerebrocortical neurons in rats

Abstract: Solvent abuse during pregnancy may cause "fetal solvent syndrome", which is characterized by mild brain atrophy and associated with behavioral, cognitive, and emotional abnormalities. The present study investigated whether solvent inhalation during the preweaning period (P2-P21) alters the morphological maturation of frontal, parietal, and occipital cortical neurons. Twelve hours after delivery (postnatal day 0, P0), litters were cross-fostered, culled to 8 pups/dam and housed together with a dam in standard l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…34 Maternal benzene exposure increased risks for spina bifida 35 and was associated with reductions in a mental development index. 36 Possible mechanisms of neurodevelopmental toxicity for toluene, based on studies of abusive use, include suppressed immune functions 37 and oxidative-stress mechanisms, 38 as well as morphological 39 and functional brain receptor interferences that during brain development may lead to neurobehavioral disturbances. 40 Thus, several of the pollutants we found to be related to autistic disorder plausibly interfere with the developing nervous system in utero.…”
Section: Discussionmentioning
confidence: 99%
“…34 Maternal benzene exposure increased risks for spina bifida 35 and was associated with reductions in a mental development index. 36 Possible mechanisms of neurodevelopmental toxicity for toluene, based on studies of abusive use, include suppressed immune functions 37 and oxidative-stress mechanisms, 38 as well as morphological 39 and functional brain receptor interferences that during brain development may lead to neurobehavioral disturbances. 40 Thus, several of the pollutants we found to be related to autistic disorder plausibly interfere with the developing nervous system in utero.…”
Section: Discussionmentioning
confidence: 99%
“…16 While toluene does not carry the same stigma as reporting alcohol or illicit drug misuse during pregnancy, 2 it is highly lipid soluble, readily crosses the placenta, is absorbed into both fetal and maternal fat and brain tissue, and is a known teratogen. [17][18][19] Indeed, the phrase fetal solvent syndrome is frequently used as a descriptor of the myriad of physical and behavioral effects that can develop following high levels of solvent exposure. 6,20 As with fetal alcohol syndrome, low birth weight (BW) is one of the most common physiological outcomes of prenatal solvent exposure in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced foetal weight and developmental defects have been observed after maternal n-hexane exposure during pregnancy (Daughtrey et al, 1994;Marks et al, 1980;Stoltenburg-Didinger et al, 1990). A recent study also reported that n-hexane inhalation during the period of brain growth impaired the nervous centralis (Pascual et al, 2010). Nonetheless, few studies have focused on reproductive disorders in adult females after in utero n-hexane exposure.…”
Section: Introductionmentioning
confidence: 99%